CHANGE AND POLITICISATION OF LITHUANIAN GOVERNMENT AGENCIES AND AGENCIES UNDER THE MINISTRIES - Bogušinskaitė, Irena; Nakrošis, Vitalis (Politologija, 2014)
This article analyses the change and politicisation of management in the Lithuanian government agencies and agencies under the ministries in the period 1990–2012. Changes in de jure politicisation of the higher civil service depended on structural and civil service reforms. The start of Lithuania’s accession to the EU marked a decline in structural politicisation, but de facto politicisation increased throughout this period. However, the politicisation trend was opposite during the 2008–2012 Government term: structural politicisation faced an upward trend, while actual politicisation was going down. Our analysis of the Lithuanian agency politicisation also revealed some differences in the pattern of politicisation according to the Lithuanian political parties. The Lithuanian Social Democratic Party more frequently pursues the strategy of de facto politicisation by recruiting agency heads involved in its political activities, while the Homeland Union (Lithuanian Christian Democrats) tends to adopt the structural form of politicisation by using government-wide civil service reforms to dismiss the incumbent managers. This research indicated that de facto politicisation of the Lithuanian agencies is relatively small with only 19.1% of all agency heads engaged in party networks. However, this measure of politicisation is more pesimistic than optimistic – it ispossible the higher civil service employs more politically affiliated managers than our analysis based on personal biographies was able to detect. Furthermore, there is variation across different types of agencies. Heads of the government agencies who acted as political appointees at certain periods of time were more politicised than managers in charge of the ministerial agencies who held career civil service positions more frequently. The turnover of agency managers is best explained by alterations of ruling majorities and governments, taking into account more the intensive turnover of agency managers during the Lithuanian governments controlled by the Lithuanian Social Democratic Party. Cases of one government agency and one agency under the ministries indicated how their managers were replaced after actual changes of government. However, there is no single straightforward explanation of politicisation. First, politicisation of the agency management could be explained in terms of certain ‘push’ factors: politicisation is associated with party entrenchment in power and density of the party networks. Political parties with longer government experience have more opportunities to make use of political appoitments. Second, politicisation is linked to some ‘pull’ factors: party patronage is exercised more frequently over more politically salient areas of public services. Therefore, the mix of political and administrative factors can be used to understand the change and politicisation of the Lithuanian agency management. On the one hand, the political parties that are better entrenched in power possess longer lists of loyal candidates for filling up managerial positions in the Lithuanian agencies. On the other hand, political parties tend to control the performance of more salient agencies through politically motivated appointments and dismissals. However, it is politicians’ beliefs and their power to exercise party patronage that brings politicisation in the higher civil service. The future research of politicisation can assess how civil service legislation and its enforcement affect the dynamics of politicisation in the Lithuanian agencies. Also, it could be useful to examine the change and politicisation of management in other Lithuanian public sector organisations.